Tindak Tutur Komisif dalam Dorama Alice in Borderland Season 1 Karya Haro Aso - Agnes, Monica; Suciaty, Prisyanti (YASIN, 2024)
This research aims to examine in more depth the function and form of commissive speech act sentences in the drama "Alice in Borderland Season 1" by Haro Aso. This research is qualitative research with descriptive methods. The method used in this research is the observation method with an advanced technique, namely the note-taking technique. This research uses the theory of the function of commissive speech acts according to Searle, the theory of sentence form by Yule, and the theory of context by Hymes. After data collection and analysis, it were found that the guarantee function 8 data, the promise function in 5 data, the refusal function in 9 data, the threat function in 4 data, the volunteer function in 5 data, and the offer function in 1 data. For sentence form, declarative were found in 24 data, imperative sentences in 4 data, and interrogative sentences in 4 data. The most dominant function identified is refusal, because the characters in the story often have to refuse requests that could endanger their lives. The most common sentence form is declarative, indicating that statements and explanations are frequently used in dialogue. This study underscores that the story's context, in which characters must survive dangerous games, significantly influences the type of commissive speech acts that arise. By utilizing theories from Searle, Yule, and Hymes, this research successfully identifies and explains the functions and forms of commissive speech acts, providing a deeper understanding of the communication dynamics in the drama.